The two cultures of English : literature, composition, and the moment of rhetoric - Maxwell, Jason (Fordham University Press, 2019)
Examines the discipline of English in North American universities in the late twentieth and early twenty-first centuries with special attention directed toward the relationship between Rhetoric and Composition and literary theory.